IDENTIFIKASI GULMA PADA DUA TIPE PERKERASAN TAMAN (KONBLOK DAN GRASBLOK) - Siti Nurisjah; A. Pieter Lontoh (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1995)
Weed constitute one the main problems encountered in urban parks, including those growing on paved park grounds, because in addition to impairing the beauty of the parks they also reduced their function and durability. By weed inventory on park grounds management actions can be planned and conducted Field observation were carried out for two months at the